Developing Quantitative Assessment Metrics for Determining the Intelligence Level of a Human-Computer Interface - El Zarka, Ahmed (2014)
A Master of Science thesis in Computer Engineering by Ahmed El Zarka entitled, "Developing Quantitative Assessment Metrics for Determining the Intelligence Level of a Human-Computer Interface," submitted in January 2014. Thesis advisor is Dr. Tarik Ozkul. Available are both soft and hard copies of the thesis.